2019
DOI: 10.1038/s41598-018-37589-1
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel derived boehmite nanostructures is a versatile nanoplatform for biomedical applications

Abstract: Alumina is one of the most promising carriers for drug delivery due to the long history of its usage as a vaccine adjuvant. Sol-gel synthesis provides excellent conditions for entrapment of biomolecules within an inorganic cage providing stabilization of proteins under the extremal conditions. In this paper, we show in vitro investigation of monodisperse alumina xerogel nanocontainers (AXNCs) using bovine serum albumin as a model protein entrapped in sol-gel alumina building blocks. Particularly, dose and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…In addition to direct DNA damage under the influence of NPs, there are also data on increasing the efficiency of horizontal transfer of genetic material when exposed to NPs. It has been shown that Al 2 O 3 , AlOOH, TiO 2 , SiO 2 , and Fe 2 O 3 NPs can contribute to the conjugating transfer of plasmid (up to 20–100 times) [ 159 , 160 , 161 ]. It is important to note that the transfer increased inside the species or genus of bacteria.…”
Section: Potential Adverse Effects Of the Broad Implementation Of mentioning
confidence: 99%
“…In addition to direct DNA damage under the influence of NPs, there are also data on increasing the efficiency of horizontal transfer of genetic material when exposed to NPs. It has been shown that Al 2 O 3 , AlOOH, TiO 2 , SiO 2 , and Fe 2 O 3 NPs can contribute to the conjugating transfer of plasmid (up to 20–100 times) [ 159 , 160 , 161 ]. It is important to note that the transfer increased inside the species or genus of bacteria.…”
Section: Potential Adverse Effects Of the Broad Implementation Of mentioning
confidence: 99%
“…Among the various supports, boehmite nanoparticles are considered as outstanding solid supports because of their physical and chemical properties such as excellent thermal and chemical stability, large internal surface area and high concentration of surface OH groups. Boehmite nanoparticles have applications in a wide variety of endeavors suchz as: the preparation of sol–gel ceramics, for rheology control, as medicinal desiccants and their carrier, as absorbents, for coatings, in electrochemical sensors, as vaccine adjuvants, in the petrochemical industry and most widely used as catalysts and catalyst carriers . More importantly, the immobilization of transition metal complexes on the nano‐boehmite surface has been rarely reported in the literature for the purpose of synthesizing heterogeneous catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Some research is based on different properties such as optical [33], electrical [34], mechanical properties [35] of boehmite those are showing its multi-dimensional usability. Biocompatibility is another major advantage of selecting boehmite for any application [36]. Boehmite was reported as a promising dental and orthopedic material due to its biocompatibility and bioavailability [37,38].…”
Section: Introductionmentioning
confidence: 99%